Predictors of dietary and fluid non‐adherence in Jordanian patients with end‐stage renal disease receiving haemodialysis: a cross‐sectional study. Issue 1 (12th June 2012) - Khalil, Amani A; Darawad, Muhammad; Al Gamal, Eklas; Hamdan‐Mansour, Ayman M; Abed, Mona A
<x xml:space="preserve">Abstract</x> Aims and objectives. The purpose of this study is to provide insight into the relationship between dietary and fluid non‐adherence, depressive symptoms, quality of life, perceived barriers and benefits of exercise, and perceived social support among Jordanian patients with end‐stage renal disease receiving haemodialysis using Pender's health promotion model. Background. Non‐adherence to dietary and fluid restrictions is a leading cause of treatment failure and poor outcomes in end‐stage renal disease. Yet, factors that interfere with the patients' ability to follow their dietary restrictions are unknown. Design. A descriptive, correlational, cross‐sectional design was used. Methods. Jordanian patients (n = 190) with end‐stage renal disease receiving haemodialysis from three main Jordanian cities were included. The dialysis diet and fluid nonadherence questionnaire, Beck Depression Inventory‐II, Quality Of Life Index, Dialysis Patient‐Perceived Exercise Benefits and Barriers Scale, and the Multidimensional Perceived Social Support were employed to measure the key variables. Results. Patients were more likely men with mean age of 48·2 ± 14·9. Only 27% of the patients showed full commitment to diet guidelines and 23% to fluid guidelines during the last 14 days. Depression (M = 18·8 ± 11·4) had significant negative association with quality of life (importance and satisfaction) (r = −0·60, r = −0·32, p = 0·001, respectively). Multiple hierarchal regressions revealed a predictive model of only two variables: age (B = −0·22, p = 0·05) and residual renal function (B = −0·23, p = 0·012) for dietary non‐adherence. Conclusions. Non‐adherence to diet and fluid guidelines association with individual characteristics, health perception and psychosocial variables should be investigated in a longitudinal design. Relationship of non‐adherence with culture‐related factors should deeply be assessed among Jordanian patients with end‐stage renal disease receiving haemodialysis. Relevance to clinical practice. Identification of the factors that may worsen dietary and fluid non‐adherence may lead to improved therapeutic interventions within the mainstream of medical practice for Jordanian patients with end‐stage renal disease receiving haemodialysis.